Blacklisted: Boundaries, Violations, and Retaliatory Behavior in the BDSM Community. Issue 8 (2nd August 2016) - Holt, Karen
ABSTRACT: This qualitative ethnographic study sought to gain insight into how participants in the Bondage/Discipline/Sadomasochism (BDSM) community negotiate and maintain boundaries in order to engage in mutually satisfying BDSM activities. Additionally, this study explored how boundary violations are handled by a community stigmatized by the larger culture. Results indicated that participants employ methods to keep BDSM play 'safe, sane, and consensual', although boundary violations do occur. These violations are handled internally by appointed community members and participants may engage in retaliatory behavior, with the occasional member employing violence. Implications of the research and future avenues for exploration are discussed.